2018
DOI: 10.1063/1.5034470
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of uranium plasma plume dynamics in atmospheric oxygen produced via femtosecond laser ablation

Abstract: Laser ablation is an easily accessible method of producing metallic plasmas in reactive, atmospheric environments. The use of laser ablation for the study of uranium plasma chemistry in atmospheric ablation plumes is highly relevant for nuclear forensics and standoff detection, but the behavior of such systems is currently not well understood. One of the main difficulties in studying these systems is that the already considerable complexity of plume dynamics in vacuum conditions is further enhanced by shockwav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Although, to our knowledge, no spectra of am-UO x have been reported below 600 cm −1 , many uranium-containing molecules produce U–O stretching modes near 500 cm −1 giving additional support for this assignment 46 , 49 . Furthermore, plume dynamic modeling of laser ablated uranium suggests higher oxides (e.g., UO 3 ) will form at the outer edge of the plume-atmosphere interface 50 , in agreement with the observed major products here. As previously mentioned, Koroglu et al 23 conclude α-UO 3 is produced when uranium nitrate and O 2 are passed through an ICP and allowed to cool.…”
Section: Discussionsupporting
confidence: 85%
“…Although, to our knowledge, no spectra of am-UO x have been reported below 600 cm −1 , many uranium-containing molecules produce U–O stretching modes near 500 cm −1 giving additional support for this assignment 46 , 49 . Furthermore, plume dynamic modeling of laser ablated uranium suggests higher oxides (e.g., UO 3 ) will form at the outer edge of the plume-atmosphere interface 50 , in agreement with the observed major products here. As previously mentioned, Koroglu et al 23 conclude α-UO 3 is produced when uranium nitrate and O 2 are passed through an ICP and allowed to cool.…”
Section: Discussionsupporting
confidence: 85%
“…In the past, those features were interpreted as arising mostly from a complex, unresolved atomic emission spectrum [41]. Recently, it has been shown that the unresolved features of uranium oxides contribute to a notable background in the emission spectrum of uranium-containing plasmas formed in the presence of oxygen [41,42]. These emission features from certain gas-phase uranium oxides heavier than uranium monoxide (U x O y , such that x ≥ 1 and y > 1, e.g., UO 2 , UO 3 , U 3 O 8 ) are still largely unidentified [43] and remain the subject of current studies.…”
Section: Uranium Spectrummentioning
confidence: 99%
“…[18][19][20] Moreover, LA of U in reactive environments and the formation of molecules add a large number of additional spectral lines, which often overlap to result in an unresolved broad spectrum. 21,22 The high density of states in high-Z molecules produces fine features which interfere with the measurement of the atomic and ionic emission spectra. In such a dense and complex system, the choice of emission lines plays an important role in quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%